2020
DOI: 10.1136/jclinpath-2020-206471
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and adiponectin receptor 1 expression proteins levels are modified in breast cancer in postmenopausal women with obesity

Abstract: AimTo analyse the expression of adiponectin (ADIPOQ), and its receptors ADIPOR1 and ADIPOR2, in breast cancer tissue of postmenopausal women with different body mass indexes (BMIs).Subjects and methodsOne hundred and fifty postmenopausal Mexican-Mestizo women with breast cancer were included. BMI was determined in each case. To carry out qualitative and semiquantitative assessments of protein expression by immunohistochemistry, the H-Score method was used, through ImageJ's IHC Profiler software. Statistical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…Adiponectin may also serve roles beyond insulin sensitization in breast cancer since increased adiponectin levels have been observed at earlier stages of the disease 73 . Studies have also identified lower expression of adiponectin in obese women with breast cancer in comparison to women with normal BMI 74,75 . The expression of adiponectin receptors 1 and 2 in breast cancer tissue as it relates to BMI is complicated as Orozco‐Arguelles et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Adiponectin may also serve roles beyond insulin sensitization in breast cancer since increased adiponectin levels have been observed at earlier stages of the disease 73 . Studies have also identified lower expression of adiponectin in obese women with breast cancer in comparison to women with normal BMI 74,75 . The expression of adiponectin receptors 1 and 2 in breast cancer tissue as it relates to BMI is complicated as Orozco‐Arguelles et al.…”
Section: Methodsmentioning
confidence: 99%
“…recently demonstrated an increase in adiponectin receptor 1 in breast cancer tissue of women with higher BMI compared to those with normal BMI. This may reflect the upregulation of compensatory mechanisms in the setting of decreased adiponectin expression 74 . Increased adiponectin levels may be indicative of improved overall survival and disease‐free survival in breast cancer 73,76 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Others found an association only in post-menopausal patients [ 113 ]. Adiponectin expression in breast cancer tissue is lower in obese women, when compared with normal BMI and overweight ones [ 114 ]. Expression of the receptors AdipoR1 and AdipoR2 is also deregulated in breast cancer [ 115 ].…”
Section: Adipokines and Tnbcmentioning
confidence: 99%